The indidoneous attempt in Paraguayan criminal law (Legal journal - Research in Legal and Social Sciences, 2023)
The purpose of this research is to analyze the punishability of the inidoneous attempt in the Paraguayan Criminal Code. Attempt constitutes an advance of the punishability of the conduct to stages prior to the injury or impairment of a legal right. For this reason, the rules that establish the conditions of supunibility will be a very significant parameter on the characteristics of a given criminal system. On the other hand, in criminal dogmatics there is also a legal figure called inidoneous attempt or impossible crime, on which there is considerable conceptual disagreement as to its meaning and scope. As for the method, it is of a documentary type, with a qualitative approach, non-experimental design and dogmatic legal scope, through which, first, a position was established about the figure of the attempt and its regulation in the current criminal dogmatics. Then, a position was sought on the meaning and scope of the inidoneous attempt or impossible crime, and whether or not it is a different figure from the attempt. Subsequently, once a position was taken on its definition, an argument was made as to whether or not it should be punishable in the abstract, i.e., in light of political-criminal criteria. Finally, after establishing in a well-founded manner a criterion referring to the exposed points, it is argued that the scope of punishment established for attempt in article 26 of the Paraguayan Criminal Code and its modification, includes the inidoneous attempt.
Keywords: Inidoneous attempt; impossible crime; criminal policy; criminal system; consummation; and legal good